Composite sheet with to-be-sintered layer preset on surface as well as preparation method and application of composite sheet

By preplacing the sintered layer on a flat metal substrate and directly used for the sintering interconnection of power semiconductor devices, the problem of insufficient reliability of traditional solder in high temperature environments is solved, and the shear strength and reliability of the sintered layer are improved.

CN119786477APending Publication Date: 2025-04-08SOLDERWELL MICROELECTRONIC PACKAGING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411902036.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional tin-based solder cannot meet the reliability requirements of modern power semiconductor devices in high temperature environments, and excessive thickness of sintered metal paste will lead to collapse or pore formation, reducing bonding strength.

Method used

A composite sheet with a layer to be sintered on the surface is adopted, including a flat metal substrate and a layer to be sintered on the upper and lower surfaces thereof. By preplacing the layer to be sintered on the flat metal substrate, it is directly used for the sintered interconnection between the interconnects to avoid the problem of excessive thickness of the sintered metal paste.

Benefits of technology

The shear strength after sintering interconnects is improved, collapse and pore formation is avoided, process flow is simplified, and material costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786477A_ABST
    Figure CN119786477A_ABST
Patent Text Reader

Abstract

The invention discloses a composite sheet with a to-be-sintered layer preset on the surface and a preparation method and application of the composite sheet, and relates to the technical field of electronic packaging. The composite sheet comprises a flat metal substrate and to-be-sintered layers preset on the upper surface and the lower surface of the flat metal substrate, the thickness of the flat metal substrate ranges from 0.03 mm to 0.25 mm, the thickness of the to-be-sintered layers ranges from 0.025 mm to 0.2 mm, and the thickness ratio of the flat metal substrate to the to-be-sintered layers ranges from 0.8 to 2.5. The to-be-sintered layer contains small-particle-size nano metal powder and large-particle-size nano metal powder with the mass ratio of (5-18): 1, and the particle sizes of the small-particle-size nano metal powder and the large-particle-size nano metal powder are 40-300 nm and 500-900 nm respectively. The composite sheet can be directly used, coating and sintering of metal slurry are not needed when the composite sheet is sintered, a drying stage is not needed, the total amount of the needed metal slurry is small and the thickness is low for the same interconnection layer thickness, and the material cost can be reduced; the composite sheet is high in shear strength after sintering interconnection, and the sintering interconnection effect of the interconnection piece can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electronic packaging, and in particular to a composite sheet with a layer to be sintered pre-disposed on its surface, and a preparation method and application thereof. Background Art

[0002] The new generation of power semiconductors represented by silicon carbide and gallium nitride have the characteristics of wide bandgap, high breakdown voltage, strong thermal stability, stable switching characteristics, etc., and are widely used in rail transportation, aerospace, new energy vehicles, deep-sea deep well exploration and other fields. During service, the interconnection materials of power semiconductor devices will be subjected to severe tests such as mechanical vibration, thermal stress, high-density current and power cycle. Traditional tin-based solders can no longer meet the increasingly stringent reliability requirements, so it is urgent to develop new high-temperature resistant sintering materials and corresponding sintering processes.

[0003] Sintered metal paste has become the most promising interconnect material that can be sintered at temperatures below 300°C due to its good electrical and thermal conductivity, low-temperature sintering, high reliability and high-temperature service performance. If the area of ​​the interconnected sintered layer (referred to as the sintered layer) increases, the thickness of the sintered layer is generally required to increase accordingly to ensure the interconnection quality of the sintered layer. This is because as the area of ​​the sintered layer increases, the degree of thermal deformation of the upper and lower interconnects during the sintering process will also increase. If the sintered layer is too thin at this time, the sintered layer may not be fully in contact with some parts of the upper and lower interfaces, resulting in a decrease in the bonding strength of the sintered layer. The increase in the thickness of the sintered layer will inevitably require a larger coating thickness of the sintered metal paste, but if the thickness of the sintered metal paste is too thick, it will collapse and overflow; and the large thickness of the coated metal paste is not conducive to the volatilization and discharge of organic matter in the sintered metal paste, and will leave pores in the sintered layer, resulting in a decrease in the bonding strength of the sintered layer. Summary of the invention

[0004] The present application provides a composite sheet with a layer to be sintered pre-set on the surface, and a preparation method and application thereof. By pre-setting the layer to be sintered on the surface of a flat metal substrate, it can be directly used for sintering interconnections between interconnecting parts, avoiding the problem of collapse caused by too thick metal slurry or difficulty in volatilization of organic matter during the sintering process, and improving the shear strength after sintering interconnections.

[0005] In order to solve the above technical problems, one of the purposes of the present application is to provide a composite sheet with a layer to be sintered pre-set on the surface, comprising a flat metal substrate and layers to be sintered pre-set on the upper and lower surfaces thereof, wherein the thickness of the flat metal substrate is 0.03-0.25 mm, the thickness of the layer to be sintered is 0.025-0.2 mm, and the ratio of the thickness of the flat metal substrate to the thickness of the layer to be sintered is 0.8-2.5; the material of the flat metal substrate is at least one of copper, silver and nickel;

[0006] The sintered metal slurry for forming the sintered layer includes the following components by mass fraction: 0.8-5 parts of dispersant, 0.6-3 parts of activator, 1.5-4 parts of binder, 1.2-6 parts of diluent and 87-97 parts of nano metal powder, wherein the nano metal powder includes small-particle size nano metal powder and large-particle size nano metal powder in a mass ratio of (5-18):1, the D50 particle size of the small-particle size nano metal powder is 40-300nm, and the D50 particle size of the large-particle size nano metal powder is 500-900nm.

[0007] The composite sheet with a layer to be sintered pre-set on the surface of the present application has layers to be sintered pre-set on both sides of the flat metal substrate. The material of the metal substrate is at least one of copper, silver and nickel, and its ductility, melting point and thermal conductivity are relatively high. It can also be sintered and interconnected with the sintered metal slurry, effectively reducing the required coating thickness of the sintered metal slurry. It is directly placed between the upper and lower interconnecting parts for sintering and interconnecting, avoiding the problem of collapse caused by too thick coating thickness of the sintered metal slurry when directly sintering and interconnecting; and it also avoids the problem that the thickness of the coated sintered metal slurry is large, which is not conducive to the volatilization and discharge of organic matter in the sintered metal slurry, and will leave pores in the sintered layer, thereby causing the bonding strength of the sintered layer to decrease; in addition, the composite sheet with a layer to be sintered pre-set on the surface of the present application can be used directly, without the need to coat the sintered metal slurry when in use, and without the need to go through the sintered metal slurry drying stage, so it is easy to use; and using the product of the present application, the total amount of metal slurry required for the same interconnection layer thickness is small, which can greatly reduce the material cost.

[0008] In addition, the large-particle nano-metal powder in the sintered metal slurry acts as a skeleton to reduce the agglomeration of the nano-metal powder and reduce the initial grain defects, while the small-particle nano-metal powder has a certain bonding function and can be used to bond the large-particle nano-metal powder, thereby achieving the goal of not increasing the sintering peak temperature but also increasing the initial stacking density, thereby increasing the shear strength of the sintered layer.

[0009] As a preferred embodiment, the nano metal powder is at least one of copper powder, silver-plated copper powder, silver powder and silver-plated nickel powder.

[0010] As a preferred embodiment, the small-particle nano-metal powder comprises silver powder and silver-plated nickel powder in a mass ratio of 11:2; and / or the large-particle nano-metal powder comprises silver powder and silver-plated nickel powder in a mass ratio of 9:1.

[0011] As a preferred embodiment, the mass ratio of the small-particle nanometal powder to the large-particle nanometal powder is in the range of any one or any two of 5:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, and 18:1, preferably (8-15):1.

[0012] If the proportion of small-particle nanometal powder in the sintered metal slurry is too high and the proportion of large-particle nanometal powder is too low, the risk of nanometal powder agglomeration will increase and the initial grain defects will increase. If the proportion of small-particle nanometal powder in the mixed metal powder is too low and the proportion of large-particle nanometal powder is too high, on the one hand, the sintering driving force is too low, which is not conducive to sintering. On the other hand, the small-particle nanometal powder cannot effectively bond to the large-particle nanometal powder and cannot fill the pores between the large-particle nanometal powders, which will reduce the initial stacking density and cause the shear strength of the sintered layer to decrease. Therefore, the mass ratio of small-particle nanometal powder to large-particle nanometal powder is preferably (5-18):1.

[0013] As a preferred embodiment, the particle size D50 of the small-particle nano-metal powder is in the range of any one or any two of 40 nm, 50 nm, 100 nm, 150 nm, 200 nm, and 300 nm, preferably 50-200 nm.

[0014] As a preferred embodiment, the particle size D50 of the large-particle nano-metal powder is in the range of any one or any two of 500nm, 550nm, 600nm, 650nm, 700nm, and 900nm, preferably 600-800nm.

[0015] If the particle size of the small-sized nano-metal powder in the sintered metal slurry is too small, the nano-metal powder will be difficult to disperse in the sintered metal slurry and will easily agglomerate; if the particle size of the small-sized nano-metal powder is too large, the small-sized nano-metal powder cannot effectively wrap and bond the large-sized nano-metal powder, and cannot fill the pores between the large-sized nano-metal powders, which will reduce the initial stacking density and cause the shear strength of the sintered layer to decrease. If the particle size of the large-sized nano-metal powder is too small, its skeleton in the sintered metal slurry will be too small, which is not conducive to the dispersion of the small-sized nano-metal powder in the sintered metal slurry; if the particle size of the large-sized nano-metal powder is too large, the sintering driving force will be too low and not conducive to sintering, causing the shear strength after sintering to decrease, so the D50 particle size of the small-sized nano-metal powder is preferably 40-300nm, and the D50 particle size of the large-sized nano-metal powder is preferably 500-900nm.

[0016] As a preferred embodiment, the thickness of the flat metal substrate is within the range of any one or any two of 0.03 mm, 0.05 mm, 0.07 mm, 0.09 mm, 0.12 mm, 0.15 mm, 0.17 mm, 0.2 mm, 0.23 mm, and 0.25 mm.

[0017] As a preferred solution, the thickness of the flat metal substrate is 0.05-0.15 mm.

[0018] If the thickness of the flat metal substrate in the composite sheet of the present application is too thin, the processing cost will be too high; secondly, if the flat metal substrate is too thin, the thermal expansion and contraction deformation of the flat metal substrate during the sintering process will cause peeling from the sintered layer, resulting in poor shear strength of the sintered layer; and if the thickness of the flat metal substrate is too thick, when the metal foil strip is punched into a flat metal substrate, the edge of the flat metal substrate will have an arc, the flatness of the flat metal substrate will be poor, and the shear strength of the sintered layer will also be poor. Therefore, the thickness of the flat metal substrate is preferably 0.03-0.25mm.

[0019] As a preferred embodiment, the thickness of the layer to be sintered is any one of or any two of 0.025 mm, 0.05 mm, 0.07 mm, 0.09 mm, 0.11 mm, 0.13 mm, 0.15 mm, 0.17 mm, and 0.2 mm.

[0020] As a preferred solution, the thickness of the layer to be sintered is 0.04-0.12 mm.

[0021] If the thickness of the layer to be sintered on the flat metal substrate of the present application is too thin, it will lead to poor adhesion to the upper and lower interfaces during sintering, resulting in poor shear strength; if the thickness of the layer to be sintered on the flat metal substrate is too thick, on the one hand, it will lead to poor adhesion of the layer to be sintered on the flat metal substrate and easy to fall off the flat metal substrate, and on the other hand, it will cause the sintered layer after sintering to be delaminated and collapsed, which will also lead to poor shear strength. Therefore, the thickness of the layer to be sintered is preferably 0.025-0.2mm.

[0022] As a preferred solution, the thickness of the layer to be sintered on the upper surface and the lower surface of the flat metal substrate can be the same or different, preferably the same. When the thickness of the layer to be sintered on the upper surface and the lower surface of the flat metal substrate is the same, the flat metal substrate is located at the center of the composite sheet with the layer to be sintered pre-set on the surface, and the sintering interconnection effect of the composite sheet with the layer to be sintered pre-set on the surface will be better.

[0023] As a preferred embodiment, the ratio of the thickness of the flat metal substrate to the thickness of the layer to be sintered is in the range of any one or any two of 0.8, 1, 1.25, 1.5, 1.67, 2, and 2.5.

[0024] As a preferred solution, the ratio of the thickness of the flat metal substrate to the thickness of the layer to be sintered is 1-2.

[0025] If the ratio of the thickness of the flat metal substrate to the thickness of the layer to be sintered in the present application is too small, the thickness of the layer to be sintered is large and the thickness of the metal substrate is small. The force generated by the layer to be sintered before sintering will pull and bend the flat metal substrate. The deformation caused by thermal expansion and contraction of the flat metal substrate during the sintering process will also cause the sintered layer to peel off, resulting in poor shear strength; and if the ratio of the thickness of the flat metal substrate to the thickness of the layer to be sintered on the flat metal substrate is too large, the thickness of the layer to be sintered is small and the thickness of the metal substrate is large. When the metal foil strip is punched into a flat metal substrate, the edge of the flat metal substrate will have an arc, increasing the risk of poor flatness of the flat metal substrate. The small thickness of the layer to be sintered cannot effectively bond to the metal substrate with poor flatness, resulting in poor shear strength of the sintered layer after sintering. Therefore, the ratio of the thickness of the flat metal substrate to the thickness of the layer to be sintered is preferably 0.8-2.5.

[0026] As a preferred embodiment, the dispersant is at least one of polydiallyldimethylammonium chloride, polyacrylamide, vinylpyrrolidone and sodium dodecyl sulfate.

[0027] As a preferred embodiment, the active agent is at least one of glutaric acid, adipic acid, citric acid and rosin acid.

[0028] As a preferred embodiment, the binder is at least one of ethyl cellulose and pinene alcohol.

[0029] As a preferred embodiment, the diluent is at least one of alcohol, ether, ester or hydrocarbon.

[0030] The dispersant is used to evenly disperse the nano-metal powder in the sintered metal slurry, the activator is used to remove the oxide layer of the nano-metal powder, the flat metal substrate and the sintering interface, the binder is used to make the sintered metal slurry adhere to the flat metal substrate, and the diluent is used to adjust the viscosity of the sintered metal slurry. By selecting the appropriate types and proportions of the dispersant, activator, binder and diluent, the nano-metal powder can be fully dispersed in the sintered metal slurry, the sintered metal slurry has a moderate viscosity and is easy to coat, and finally a sintered layer of good quality is obtained after sintering.

[0031] As a preferred embodiment, the dispersant includes polydiallyldimethylammonium chloride, polyacrylamide, vinylpyrrolidone and sodium dodecylsulfonate in a mass ratio of 2:1:4:2.

[0032] As a preferred embodiment, the active agent includes glutaric acid, adipic acid, citric acid and rosin acid in a mass ratio of 1:1:3:5.

[0033] As a preferred embodiment, the binder comprises ethyl cellulose and pinene alcohol in a mass ratio of 3:5.

[0034] As a preferred embodiment, the diluent includes propylene glycol, dibutyl ether, diethylene glycol ethyl ether acetate and octane in a mass ratio of 5:2:1:4.

[0035] In order to solve the above technical problems, the second object of the present application is to provide a method for preparing a composite sheet with a layer to be sintered pre-set on the surface, comprising the following steps:

[0036] (1) Softening and annealing the metal foil strip at a temperature ≥ 200° C. in a reducing gas atmosphere, and punching the metal foil strip to obtain a flat metal substrate of a desired thickness;

[0037] (2) The components of the sintered metal slurry are mixed evenly, coated on the upper and lower surfaces of the flat metal substrate, and dried to obtain a composite sheet with a pre-sintered layer on the surface.

[0038] As a preferred embodiment, in step (1), the temperature of the softening annealing is any one of or any two of 200°C, 220°C, 250°C, 270°C, 300°C, 330°C, 350°C, 380°C, 400°C, 450°C, and 500°C.

[0039] As a preferred embodiment, in step (1), the softening annealing time is 1-2 hours.

[0040] As a preferred embodiment, in step (1), the softening annealing time is within the range of any one or any two of 1 h, 1.1 h, 1.5 h, 1.8 h, and 2 h.

[0041] As a preferred embodiment, in step (1), the temperature of the softening annealing is 200-500°C.

[0042] The annealing temperature of the present application can not only soften the metal foil strip to remove stress under low energy consumption, but also fully remove the oxide layer on the surface of the metal foil strip without secondary oxidation. Therefore, the annealing temperature is selected to be ≥200°C, preferably 200-500°C, and more preferably 300-500°C. Too high a temperature will cause greater energy loss.

[0043] As a preferred embodiment, in step (1), the reducing gas is a mixed gas of 3%-6% hydrogen and 94%-97% nitrogen by volume.

[0044] As a preferred embodiment, in step (1), the volume of hydrogen in the reducing gas can be any one of 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% or any two of the range values, and the volume of nitrogen can be any one of 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97% or any two of the range values.

[0045] As a preferred embodiment, in step (2), the vacuum degree of drying is ≤200 Pa and the temperature is 80-120°C.

[0046] As a preferred embodiment, in step (2), the vacuum degree of drying is in the range of any one or any two of 10Pa, 30Pa, 50Pa, 70Pa, 90Pa, 110Pa, 130Pa, 150Pa, 180Pa, and 200Pa.

[0047] As a preferred embodiment, in step (2), the drying temperature is in the range of any one or any two of 80°C, 90°C, 100°C, 110°C, and 120°C.

[0048] As a preferred solution, in order to avoid the influence of impurities on the metal foil on the composite sheet with a pre-set sintering layer on the surface, the metal foil needs to be cleaned before softening annealing. The cleaning steps are: placing the metal foil in a degreasing agent for ultrasonic cleaning to remove grease on the surface of the metal foil, then ultrasonically cleaning the metal foil with water, and finally drying the moisture on the surface of the metal foil with hot air at 80-100°C.

[0049] In order to solve the above technical problems, the third object of the present application is to provide an application of a composite sheet with a pre-set layer to be sintered on the surface in the field of preparing electronic packaging sintered interconnection materials.

[0050] Compared with the prior art, this application has the following beneficial effects:

[0051] 1. The composite sheet of the present application has pre-set layers to be sintered on both sides of the flat metal substrate. The material ductility, melting point and thermal conductivity of the metal substrate are relatively high, and can be sintered and interconnected with the sintered metal slurry, effectively reducing the required coating thickness of the sintered metal slurry, and can be directly placed between the upper and lower interconnecting parts for sintering and interconnecting, avoiding the problem of collapse caused by the sintered metal slurry being too thick, and also avoiding the problem of the coated sintered metal slurry being too thick, which is not conducive to the volatilization and discharge of organic matter in the sintered metal slurry, and will leave pores in the sintered layer, thereby causing the bonding strength of the sintered layer to decrease.

[0052] 2. The composite sheet with a pre-set sintering layer on the surface of the present application can be used directly without coating the sintering metal slurry when in use, and there is no need to go through the sintering metal slurry drying stage, so it is easy to use; and using the product of the present application, for the same interconnection layer thickness, the total amount of metal slurry required is small, which can greatly reduce the material cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1: This is a picture of a composite sheet with a pre-sintered layer on its surface prepared by method S4 of Example 1 of the present application, in which a sintered metal slurry is coated with a 0.4 mm thick slurry;

[0054] Figure 2 : This is a picture of a composite sheet with a pre-sintered layer on its surface prepared by method S4 of Example 1 of the present application, wherein the sintered metal slurry is coated with a 0.35 mm thick slurry;

[0055] Figure 3 : This is a picture of a composite sheet with a pre-sintered layer on its surface prepared by method S4 of Example 1 of the present application, in which a sintered metal slurry is coated with a slurry with a thickness of 0.3 mm;

[0056] Figure 4 : This is a picture of a composite sheet with a pre-sintered layer on its surface prepared by method S4 of Example 1 of the present application, wherein the sintered metal slurry is coated with a 0.25 mm thick slurry;

[0057] Figure 5 : This is a picture of a composite sheet with a layer to be sintered pre-set on its surface in Example 33 of the present application. DETAILED DESCRIPTION

[0058] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0059] It should be understood that the terms described in the present application are only for describing a particular embodiment and are not intended to limit the present application. In addition, for the numerical range in the present application, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0060] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the field described in the present application. Although the present application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.

[0061] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present application description without departing from the scope or spirit of the present application. Other embodiments derived from the present application description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0062] As used herein:

[0063] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0064] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0065] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood to specifically invent all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is invented separately. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0066] In the present application, unless otherwise specified, the parts and percentages are all based on mass.

[0067] "Parts by mass" refers to the basic unit of measurement that indicates the proportional relationship of the masses of multiple components. 1 part can represent any unit mass. It should not be misunderstood that, unlike the number of parts by mass, the sum of the parts by mass of all components is not limited to 100 parts.

[0068] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0069] The “sintered layer” refers to a layer formed after sintering a composite sheet having a layer to be sintered pre-disposed on its surface.

[0070] "Sintering metal paste" refers to a paste-like slurry that is coated on a flat metal substrate and then dried to form a layer to be sintered.

[0071] The “thickness of the layer to be sintered” refers to either the thickness of the layer to be sintered on the upper surface of the flat metal substrate or the thickness of the layer to be sintered on the lower surface of the flat metal substrate.

[0072] In order to further illustrate the present application, the composite sheet with a pre-sintered layer on the surface provided by the present application and its preparation method and application are described in detail in combination with the examples below, but they should not be understood as limiting the scope of protection of the present application. The raw materials used in the following application examples and comparative examples, unless otherwise specified, can be obtained from the market, and the same raw materials are used in parallel experiments.

[0073] Example 1

[0074] A composite sheet with a layer to be sintered pre-disposed on the surface, comprising a flat metal substrate and layers to be sintered located on the upper and lower surfaces of the flat metal substrate, respectively, the thickness of the flat metal substrate is 0.1 mm, and the thickness of the layers to be sintered after drying is 0.08 mm, so that the thickness ratio of the flat metal substrate to the layers to be sintered is 1.25;

[0075] The flat metal substrate is made of copper, and the sintered metal slurry used to form the sintered layer includes 2.8wt% dispersant, 2wt% activator, 3.2wt% binder, 4.5wt% diluent and the remainder of nano copper powder;

[0076] The dispersant comprises polydiallyldimethylammonium chloride, polyacrylamide, vinylpyrrolidone and sodium dodecylsulfonate in a mass ratio of 2:1:4:2, the active agent comprises glutaric acid, adipic acid, citric acid and rosin acid in a mass ratio of 1:1:3:5, the binder comprises ethyl cellulose and pinene alcohol in a mass ratio of 3:5, and the diluent comprises propylene glycol, dibutyl ether, diethylene glycol ethyl ether acetate and octane in a mass ratio of 5:2:1:4;

[0077] The nano copper powder includes small-particle nano copper powder and large-particle nano copper powder in a mass ratio of 12:1. The particle size D50 of the small-particle nano copper powder is 65 nm, and the particle size D50 of the large-particle nano copper powder is 700 nm.

[0078] The method for preparing the composite sheet with a layer to be sintered pre-disposed on the surface thereof comprises the following steps:

[0079] S1: Use a degreasing agent to ultrasonically clean a copper foil tape with a thickness of 0.1 mm and a width of 60 mm to remove grease from the surface of the copper foil tape, then use deionized water to ultrasonically clean it, and finally use hot air at 100°C to dry the moisture on the surface of the copper foil tape;

[0080] S2: placing the copper foil strip in a vacuum annealing furnace, and performing softening annealing at a temperature of 350° C. under reducing gas conditions, wherein the reducing gas is a mixed gas of 5wt% hydrogen and 95wt% nitrogen, to remove the oxide layer on the surface of the copper foil strip;

[0081] S3: punching the copper foil strip into a flat copper substrate with a size of 25 mm×25 mm×0.1 mm;

[0082] S4: mixing nano copper powder, dispersant, activator, binder and diluent evenly to prepare sintered metal slurry;

[0083] S5: coating the sintered metal slurry on the upper and lower surfaces of the flat copper substrate, and then drying it at a vacuum degree of 200 Pa and a temperature of 100° C. for 20 minutes to form a sintered layer of a predetermined thickness on the upper and lower surfaces of the flat copper substrate to obtain a composite sheet.

[0084] Example 2

[0085] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.08 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 1.

[0086] Example 3

[0087] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.16 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 2.

[0088] Example 4

[0089] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.064 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 0.8.

[0090] Example 5

[0091] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.2 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 2.5.

[0092] Example 6

[0093] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.05 mm, and the thickness of the layer to be sintered is 0.04 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 1.25.

[0094] Example 7

[0095] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.15 mm, and the thickness of the layer to be sintered is 0.12 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 1.25.

[0096] Example 8

[0097] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.03 mm, and the thickness of the layer to be sintered is 0.025 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 1.2.

[0098] Example 9

[0099] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein the steps in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.25 mm, and the thickness of the layer to be sintered is 0.2 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 1.25.

[0100] Example 10

[0101] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein the steps in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thicknesses of the layers to be sintered on the upper and lower surfaces of the flat metal substrate are 0.06 mm and 0.1 mm, respectively, so that the thickness ratios of the flat metal substrate and the layers to be sintered on the upper and lower surfaces are 1.67 and 1, respectively.

[0102] Embodiment 11

[0103] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the mass ratio of small-particle nano-copper powder to large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 8:1.

[0104] Example 12

[0105] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the mass ratio of small-particle nano-copper powder to large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 15:1.

[0106] Example 13

[0107] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the mass ratio of small-particle nano-copper powder to large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 5:1.

[0108] Embodiment 14

[0109] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the mass ratio of small-particle nano-copper powder to large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 18:1.

[0110] Embodiment 15

[0111] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the small-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 50 nm.

[0112] Example 16

[0113] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the small-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 200 nm.

[0114] Embodiment 17

[0115] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the small-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 40 nm.

[0116] Embodiment 18

[0117] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the small-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 300 nm.

[0118] Embodiment 19

[0119] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 600nm.

[0120] Embodiment 20

[0121] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 800nm.

[0122] Embodiment 21

[0123] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 500 nm.

[0124] Embodiment 22

[0125] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 900 nm.

[0126] Embodiment 23

[0127] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in S2, the softening annealing temperature is 300°C.

[0128] Embodiment 24

[0129] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in S2, the softening annealing temperature is 200°C.

[0130] Embodiment 25

[0131] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in S2, the softening annealing temperature is 500°C.

[0132] Embodiment 26

[0133] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the sintered metal slurry used to form the layer to be sintered includes a mass fraction of 0.8wt% dispersant, 3wt% activator, 4wt% binder, 6wt% diluent and the remainder of nano copper powder.

[0134] Embodiment 27

[0135] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the sintered metal slurry used to form the layer to be sintered includes a mass fraction of 5wt% dispersant, 0.6wt% activator, 1.5wt% binder, 1.2wt% diluent and the remainder of nano copper powder.

[0136] Embodiment 28

[0137] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the material of the flat metal substrate is silver.

[0138] Embodiment 29

[0139] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the material of the flat metal substrate is nickel.

[0140] Embodiment 30

[0141] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the nano-copper powder in the sintered copper slurry used to form the layer to be sintered is replaced by an equal amount of nano-silver powder of the same particle size.

[0142] Embodiment 31

[0143] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the nano copper powder in the sintered copper slurry used to form the layer to be sintered is replaced by an equal amount of silver-plated copper powder of the same particle size.

[0144] Embodiment 32

[0145] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method thereof and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the large-particle-size nano-copper powder in the sintered copper slurry used to form the layer to be sintered is replaced by an equal amount of a mixture of nano-silver powder and silver-plated nickel powder with the same particle size and a mass ratio of 9:1, and the small-particle-size nano-copper powder is replaced by an equal amount of nano-silver powder and silver-plated nickel powder with the same particle size and a mass ratio of 11:2.

[0146] Embodiment 33

[0147] A composite sheet with a layer to be sintered pre-set on its surface, wherein the steps in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the material of the flat metal substrate is Ag72Cu28 (the mass ratio of Ag to Cu is 72:28), and the nano-copper powder is replaced by an equal amount of nano-silver powder of the same particle size.

[0148] Comparative Example 1

[0149] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.04 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 0.5.

[0150] Comparative Example 2

[0151] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.24 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 3.

[0152] Comparative Example 3

[0153] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein the steps in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thicknesses of the layers to be sintered on the upper and lower surfaces of the flat metal substrate are 0.04 mm and 0.16 mm, respectively, so that the thickness ratios of the flat metal substrate and the layers to be sintered on the upper and lower surfaces are 2.5 and 0.625, respectively.

[0154] Comparative Example 4

[0155] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein the steps in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.24 mm, and the thicknesses of the layers to be sintered on the upper and lower surfaces of the flat metal substrate are 0.12 mm and 0.08 mm, respectively, so that the thickness ratios of the flat metal substrate and the layers to be sintered on the upper and lower surfaces are 2 and 3, respectively.

[0156] Comparative Example 5

[0157] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.02 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 0.25.

[0158] Comparative Example 6

[0159] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the flat metal substrate is 0.4 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 5.

[0160] Comparative Example 7

[0161] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the layer to be sintered is 0.015 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 6.67.

[0162] Comparative Example 8

[0163] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thickness of the layer to be sintered is 0.3 mm, so that the thickness ratio of the flat metal substrate and the layer to be sintered is 0.33.

[0164] Comparative Example 9

[0165] A composite sheet having a layer to be sintered pre-disposed on its surface, wherein the steps in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thicknesses of the layers to be sintered on the upper and lower surfaces of the flat metal substrate are 0.015 mm and 0.145 mm, respectively, so that the thickness ratios of the flat metal substrate and the layers to be sintered on the upper and lower surfaces are 6.67 and 0.69, respectively.

[0166] Comparative Example 10

[0167] A composite sheet having a layer to be sintered pre-set on its surface, wherein the steps in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the thicknesses of the layers to be sintered on the upper and lower surfaces of the flat metal substrate are 0.3 mm and 0.1 mm, respectively, so that the thickness ratios of the flat metal substrate and the layers to be sintered on the upper and lower surfaces are 0.33 and 1, respectively.

[0168] Comparative Example 11

[0169] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the mass ratio of small-particle nano-copper powder to large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 2:1.

[0170] Comparative Example 12

[0171] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the mass ratio of small-particle nano-copper powder to large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 23:1.

[0172] Comparative Example 13

[0173] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the small-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 15 nm.

[0174] Comparative Example 14

[0175] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the small-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 400 nm.

[0176] Comparative Example 15

[0177] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 400nm.

[0178] Comparative Example 16

[0179] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the particle size D50 of the large-particle nano-copper powder in the sintered copper slurry used to form the layer to be sintered is 1000 nm.

[0180] Comparative Example 17

[0181] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the large-particle-size nano-copper powder in the sintered copper slurry used to form the layer to be sintered is replaced by an equal amount of small-particle-size nano-copper powder.

[0182] Comparative Example 18

[0183] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the small-particle-size nano-copper powder in the sintered copper slurry used to form the layer to be sintered is replaced by an equal amount of large-particle-size nano-copper powder.

[0184] Comparative Example 19

[0185] A composite sheet with a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in S2, the softening annealing temperature is 150°C.

[0186] Comparative Example 20

[0187] A composite sheet having a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the copper foil strip is not subjected to softening annealing treatment in S2, and the copper foil strip in S1 is directly punched into a flat copper substrate with a size of 25 mm×25 mm×0.1 mm in S3.

[0188] Comparative Example 21

[0189] A composite sheet having a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the sintered metal slurry used to form the layer to be sintered includes a mass fraction of 6wt% dispersant, 0.4wt% activator, 5wt% binder, 7wt% diluent and the remainder of nano copper powder.

[0190] Comparative Example 22

[0191] A composite sheet having a layer to be sintered pre-set on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the dispersant in the sintered metal slurry used to form the layer to be sintered is gelatin, the activator is sulfuric acid, the binder is glycerol, and the diluent is acetone.

[0192] Comparative Example 23

[0193] A composite sheet with a layer to be sintered pre-disposed on its surface, wherein each step in the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the material of the flat metal substrate is aluminum.

[0194] Comparative Example 24

[0195] A composite sheet with a layer to be sintered pre-disposed on the surface, comprising a flat SiC ceramic substrate and layers to be sintered located on the upper and lower surfaces of the SiC ceramic substrate, respectively, the thickness of the SiC ceramic substrate is 0.1 mm, and the thickness of the layers to be sintered after drying is 0.08 mm, so that the thickness ratio of the SiC ceramic substrate to the layers to be sintered is 1.25;

[0196] The sintering metal slurry used to form the sintered layer includes 2.8wt% dispersant, 2wt% activator, 3.2wt% binder, 4.5wt% diluent and the balance of nano copper powder;

[0197] The dispersant comprises polydiallyldimethylammonium chloride, polyacrylamide, vinylpyrrolidone and sodium dodecylsulfonate in a mass ratio of 2:1:4:2, the active agent comprises glutaric acid, adipic acid, citric acid and rosin acid in a mass ratio of 1:1:3:5, the binder comprises ethyl cellulose and pinene alcohol in a mass ratio of 3:5, and the diluent comprises propylene glycol, dibutyl ether, diethylene glycol ethyl ether acetate and octane in a mass ratio of 5:2:1:4;

[0198] The nano copper powder includes small-particle nano copper powder and large-particle nano copper powder in a mass ratio of 12:1. The particle size D50 of the small-particle nano copper powder is 65 nm, and the particle size D50 of the large-particle nano copper powder is 700 nm.

[0199] A method for preparing a composite sheet with a layer to be sintered pre-disposed on the surface thereof comprises the following steps:

[0200] S1: The size of the flat SiC ceramic substrate is 25 mm × 25 mm × 0.1 mm. The SiC ceramic substrate is die-casted by SiC powder with a particle size D50 of 2 μm.

[0201] S2: mixing nano copper powder, dispersant, activator, binder and diluent evenly to prepare sintered metal slurry;

[0202] S3: coating the sintered metal slurry on the upper and lower surfaces of the SiC ceramic substrate, and then drying it at a vacuum degree of 200 Pa and a temperature of 100° C. for 20 minutes to form a sintered layer of a predetermined thickness on the upper and lower surfaces of the SiC ceramic substrate to obtain a composite sheet.

[0203] Performance testing

[0204] 1. The sintered metal paste prepared by the preparation method S4 of Example 1 was coated on the substrate with a paste thickness of 0.4 mm, 0.35 mm, 0.3 mm and 0.25 mm. The state of the sintered metal paste after coating and before drying was as follows: Figure 1-4 shown.

[0205] 2. Shear strength test: The composite sheets prepared in the embodiment and the comparative example were placed between a silver-plated copper block with a size of 25 mm × 25 mm × 2 mm and a silver-plated copper block with a size of 40 mm × 40 mm × 2 mm, and sintered for 20 min at a pressure of 15 MPa and a temperature of 250°C to obtain a sintered body; the shear strength of the sintered layer formed by sintering the composite sheets of the embodiment and the comparative example was tested on a push-pull tester at a tensile speed of 0.7 mm / s. The greater the shear strength, the better the sintering interconnection effect.

[0206] Table 1- Shear strength of sintered layer formed after sintering of composite sheets of examples and comparative examples

[0207]

[0208]

[0209]

[0210] like Figure 1 As shown, when the sintered metal slurry of Example 1 is coated with a 0.4 mm thick slurry, it can be found that the slurry collapses and overflows more; Figure 2 As shown in Figure 1, when the 0.35 mm thick slurry is applied, the slurry collapses and overflows more frequently; Figure 3 As shown in the figure, when the 0.3mm thick slurry is applied, the overflow of the slurry tower is reduced; Figure 4 As shown in the figure, when 0.25mm thick slurry is applied, the slurry collapses and overflows significantly less, and the thickness will be reduced by about 10%-20% after drying, that is, the sintered layer thickness can reach about 0.2mm. This shows that the thickness of the sintered layer formed by drying after the sintered metal slurry is applied needs to be controlled below 0.2mm to avoid the collapse and overflow of the sintered metal slurry, because the collapsed and overflowed slurry will not only affect the shear strength of the interconnection, but may even cause bridge short circuits in the electronic components, affecting product quality.

[0211] As shown in Table 1, in the composite sheets of Examples 1-10, the thickness of the flat metal substrate is 0.03-0.25mm, the thickness of the layer to be sintered is 0.025-0.2mm, and the thickness ratio of the flat metal substrate to the layer to be sintered is between 0.8-2.5, and the shear strength is significantly better. In Comparative Examples 1-4, although the thickness of the flat metal substrate is also in the range of 0.03-0.25mm, and the thickness of the layer to be sintered is also in the range of 0.025-0.2mm, the thickness ratio of the flat metal substrate to the layer to be sintered in the composite sheet of Comparative Example 1 is significantly lower than 0.8, which is too small compared to the thickness ratio of the embodiment. At this time, the thickness of the layer to be sintered is large and the thickness of the metal substrate is small. The force generated by the layer to be sintered before sintering will pull and bend the flat metal substrate, and the deformation caused by the thermal expansion and contraction of the flat metal substrate during the sintering process will also It will cause the sintered layer to peel off, resulting in poor shear strength; the thickness ratio of the flat metal substrate and the layer to be sintered in the composite sheet of Comparative Example 2 is significantly higher than 2.5, which is too large compared to the thickness ratio of the embodiment. At this time, the thickness of the layer to be sintered is small and the thickness of the metal substrate is large. When the metal foil strip is punched into a flat metal substrate, it will cause the edge of the flat metal substrate to have a curvature, increasing the risk of poor flatness of the flat metal substrate. The thin thickness of the layer to be sintered cannot effectively bond the metal substrate with poor flatness, resulting in the shear strength of the sintered layer after sintering is still poor. In Comparative Examples 3 and 4, any side of the thickness ratio of the flat metal substrate to the layer to be sintered is significantly lower than 0.8 or higher than 2.5, and the shear strength is also poor.

[0212] The thickness of the flat metal substrate in the composite sheet of Comparative Example 5 is less than 0.03 mm. If the flat metal substrate is too thin, the thermal expansion and contraction deformation of the flat metal substrate during the sintering process will cause it to peel off from the sintered layer, resulting in poor shear strength of the sintered layer; the thickness of the flat metal substrate in the composite sheet of Comparative Example 6 is greater than 0.25 mm. If the thickness of the flat metal substrate is too thick, when the metal foil strip is punched into a flat metal substrate, the edge of the flat metal substrate will have a curvature, the flatness of the flat metal substrate will be poor, and the shear strength of the sintered layer will also be poor.

[0213] The thickness of the layer to be sintered in the composite sheet of Comparative Example 7 is less than 0.025mm. If the thickness of the layer to be sintered is too thin, it will not be firmly bonded to the upper and lower interfaces during sintering, resulting in poor shear strength. The thickness of the layer to be sintered in the composite sheet of Comparative Example 8 is greater than 0.2mm. If the thickness of the layer to be sintered is too thick, on the one hand, it will not be firmly bonded to the flat metal substrate and will easily fall off the flat metal substrate. On the other hand, it will cause the sintered layer to be delaminated and collapsed after sintering, which will also lead to poor shear strength. The thickness of the layer to be sintered in Comparative Examples 9 and 10 is less than 0.025mm or greater than 0.2mm on any side, and the shear strength is also poor.

[0214] It can be seen from Example 1 and Example 10 that when the thickness of the layers to be sintered on the upper and lower surfaces of the flat metal substrate is the same, the flat metal substrate is located at the center of the composite sheet with the layers to be sintered pre-set on the surface, and the resulting composite sheet with the layers to be sintered pre-set on the surface has a better sintering interconnection effect.

[0215] As shown in Table 1, the ratio of the small-particle size and large-particle size nano copper powder in the sintered metal slurry in Examples 1 and 11-14 is between (5-18):1, while the ratio of Comparative Example 11 is 2:1, and the ratio of Comparative Example 12 is 23:1. The shear strength of the composite sheets of Comparative Examples 11-12 after sintering is lower than that of the embodiments. This is because the proportion of small-particle size nano metal powder in the sintered metal slurry is too high and the proportion of large-particle size nano metal powder is too low, which will increase the risk of nano metal powder agglomeration and increase the initial grain defects; and if the proportion of small-particle size nano metal powder in the mixed metal powder is too low and the proportion of large-particle size nano metal powder is too high, on the one hand, it is not conducive to sintering due to the low sintering driving force, and on the other hand, the small-particle size nano metal powder cannot effectively play the role of bonding large-particle size nano metal powder, and cannot fill the pores between large-particle size nano metal powders, which will reduce the initial stacking density and cause the shear strength of the sintered layer to decrease.

[0216] As shown in Table 1, the particle size D50 of the small-particle nano copper powder in the sintered metal slurry in Examples 1 and 15-18 is between 40-300nm, while the particle size of Comparative Example 13 is smaller at 15nm, and the particle size of Comparative Example 14 is larger at 400nm, resulting in a significant decrease in the shear strength of the composite sheet after sintering. This is because the particle size of the small-particle nano metal powder in the sintered metal slurry is too small, which makes it difficult to disperse the nano metal powder in the sintered metal slurry and easy to agglomerate; and if the particle size of the small-particle nano metal powder is too large, the small-particle nano metal powder cannot effectively wrap and bond the large-particle nano metal powder, and cannot fill the pores between the large-particle nano metal powders, which will reduce the initial stacking density and cause the shear strength of the sintered layer to decrease.

[0217] As shown in Table 1, the D50 particle size of the large-particle nano copper powder in the sintered metal slurry in Examples 1 and 19-22 is between 500-900nm, while the particle size of Comparative Example 15 is smaller at 400nm, and the particle size of Comparative Example 16 is larger at 1000nm, resulting in a lower shear strength of the composite sheet after sintering. This is because if the particle size of the large-particle nano metal powder is too small, it will cause its skeleton in the sintered metal slurry to be too small, which is not conducive to the dispersion of the small-particle nano metal powder in the sintered metal slurry; and if the particle size of the large-particle nano metal powder is too large, the sintering driving force will be too low and not conducive to sintering, resulting in a decrease in shear strength after sintering.

[0218] Compared with Example 1, the sintered metal slurry in Comparative Example 17 uses small-particle nano-copper powder. When the sintered metal slurry contains only small-particle nano-metal powder, it will cause poor dispersion in the sintered metal slurry and easy agglomeration, resulting in a significant decrease in the shear strength of the composite sheets after sintering and interconnection, and the cost of manufacturing metal powder with small particle size is also high; the sintered metal slurry in Comparative Example 18 uses large-particle nano-copper powder. When the sintered metal slurry contains only large-particle nano-metal powder, the sintering driving force will be too low, which is not conducive to sintering, resulting in significantly insufficient shear strength of the composite sheets after sintering and interconnection.

[0219] As shown in Table 1, the softening annealing temperature of the copper foil in S2 of Examples 1, 23-25 ​​is between 200-500°C. The annealing temperature can not only soften the copper foil to remove stress under low energy consumption, but also fully remove the oxide layer on the surface of the metal foil strip without secondary oxidation. If the annealing temperature is too high, energy loss will be caused. If the annealing temperature is too low, the copper foil cannot be effectively softened to remove stress. The softening annealing temperature of Comparative Example 19 is relatively low. The copper foil of Comparative Example 20 is not subjected to softening annealing treatment, resulting in poor shear strength after subsequent sintering of the composite sheet.

[0220] As shown in Table 1, the flat metal substrates of Examples 1, 28-29, and 33 are copper, silver, nickel, and Ag72Cu28, respectively, which have relatively high ductility, melting point, and thermal conductivity, and can be sintered and interconnected with sintered metal slurry to improve the shear strength of the composite sheet after sintering and interconnection. Among them, the composite sheet using silver and nickel as the flat metal substrate can obtain a relatively high shear strength. The flat metal substrate of Comparative Example 23 is aluminum, and Comparative Example 24 is a SiC ceramic sheet, and the shear strength is significantly lower. This is because aluminum and ceramics are used as substrates. Under the sintering temperature conditions, a sintered interconnection layer cannot be formed. Only the adhesion caused by the residual organic matter in the sintered layer provides a weaker bonding strength. The metals do not diffuse and bond with each other, so the shear strength is extremely low. As shown in Table 1, the nano-metal powders of the sintered metal slurries in Examples 1 and 30-32 are copper powder, silver powder, silver-plated copper powder, and a mixture of silver powder and silver-plated nickel powder, respectively. It can be found that when the nano-metal powders are silver powder, silver-plated copper powder, and silver-plated nickel powder, the shear strength of the composite sheet after sintering and interconnection can be further improved. This is because silver powder, silver-plated copper powder, and silver-plated nickel powder are less likely to oxidize than copper powder, and are more conducive to sintering and interconnection, thereby improving the shear strength.

[0221] The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present application in detail. It should be understood that the above description is only a specific embodiment of the present application and is not intended to limit the scope of protection of the present application. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of protection of the present application.

Claims

1. A composite sheet with a layer to be sintered pre-set on its surface, characterized in that: It comprises a flat metal substrate and layers to be sintered pre-placed on the upper and lower surfaces thereof, wherein the thickness of the flat metal substrate is 0.03-0.25 mm, the thickness of the layer to be sintered is 0.025-0.2 mm, and the ratio of the thickness of the flat metal substrate to the thickness of the layer to be sintered is 0.8-2.5; the material of the flat metal substrate is at least one of copper, silver and nickel; The sintered metal slurry for forming the sintered layer includes the following components in parts by weight: 0.8-5 parts of a dispersant, 0.6-3 parts of an activator, 1.5-4 parts of a binder, 1.2-6 parts of a diluent, and 87-97 parts of a nano-metal powder. The nano-metal powder includes small-particle-size nano-metal powder and large-particle-size nano-metal powder in a mass ratio of (5-18):

1. The D50 particle size of the small-particle-size nano-metal powder is 40-300nm, and the D50 particle size of the large-particle-size nano-metal powder is 500-900nm.

2. A composite sheet with a pre-sintered layer on the surface as claimed in claim 1, characterized in that: The nano metal powder is at least one of copper powder, silver-plated copper powder, silver powder and silver-plated nickel powder.

3. A composite sheet with a pre-sintered layer on the surface as claimed in claim 1, characterized in that: The small-particle nano-metal powder comprises silver powder and silver-plated nickel powder in a mass ratio of 11:2; and / or the large-particle nano-metal powder comprises silver powder and silver-plated nickel powder in a mass ratio of 9:

1.

4. A composite sheet with a pre-sintered layer on the surface as claimed in claim 1, characterized in that: The mass ratio of the small-particle-size nano-metal powder to the large-particle-size nano-metal powder is (8-15):1; And / or, the particle size D50 of the small-particle nano-metal powder is 50-200 nm; And / or, the particle size D50 of the large-particle nano-metal powder is 600-800nm.

5. A composite sheet with a pre-sintered layer on the surface as claimed in claim 1, characterized in that: The thickness of the flat metal substrate is 0.05-0.15 mm, the thickness of the layer to be sintered is 0.04-0.12 mm, and / or the ratio of the thickness of the flat metal substrate to the thickness of the layer to be sintered is 1-2.

6. A composite sheet with a pre-sintered layer on the surface as claimed in claim 1, characterized in that: The dispersant is at least one of polydiallyldimethylammonium chloride, polyacrylamide, vinylpyrrolidone and sodium dodecylsulfonate; and / or, the active agent is at least one of glutaric acid, adipic acid, citric acid, and rosin acid; And / or, the binder is at least one of ethyl cellulose and terpineol; And / or, the diluent is at least one of alcohol, ether, ester or hydrocarbon.

7. A composite sheet with a pre-sintered layer on the surface as claimed in claim 1, characterized in that: The dispersant comprises polydiallyldimethylammonium chloride, polyacrylamide, vinylpyrrolidone and sodium dodecylsulfonate in a mass ratio of 2:1:4:2; and / or, the active agent comprises glutaric acid, adipic acid, citric acid and rosin acid in a mass ratio of 1:1:3:5; And / or, the binder comprises ethyl cellulose and terpineol in a mass ratio of 3:5; And / or, the diluent includes propylene glycol, dibutyl ether, diethylene glycol ethyl ether acetate and octane in a mass ratio of 5:2:1:

4.

8. A method for preparing a composite sheet with a pre-sintered layer on the surface as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Softening and annealing the metal foil strip at a temperature ≥ 200° C. in a reducing gas atmosphere, and punching the metal foil strip to obtain a flat metal substrate of a desired thickness; (2) The components of the sintered metal slurry are mixed evenly, coated on the upper and lower surfaces of the flat metal substrate, and dried to obtain a composite sheet with a pre-sintered layer on the surface.

9. The method for preparing a composite sheet with a pre-sintered layer on the surface as claimed in claim 8, characterized in that: In step (1), the softening annealing temperature is 200-500° C., and the annealing time is 1-2 h; And / or, in step (1), the reducing gas is a mixed gas of 3%-6% by volume of hydrogen and 94%-97% by volume of nitrogen; And / or, in step (2), the vacuum degree of drying is ≤200 Pa and the temperature is 80-120°C.

10. Use of a composite sheet with a pre-sintered layer on the surface as claimed in any one of claims 1 to 9 in the field of preparing electronic packaging sintered interconnection materials.